AB0326 Severity index for rheumatoid arthritis and its association with healthcare costs and biologic therapy use in turkey. (23rd January 2014) - Baser, O.; Baser, E.; Altinbas, A.; Burkan, A.
Abstract : Objectives: To apply a validated claims-based severity index for rheumatoid arthritis (SIFRA) to prevalent RA groups in Turkey to determine the effects of RA severity on healthcare costs and biologic use. Methods: Using medical and pharmacy claims and eligibility data from the Turkish national health insurance database MEDULA for RA patients in Turkey (01JUN2009-31DEC2011), prevalent RA patients age 18-99, with two RA diagnoses ≥60 days apart and continuously enrolled 1 year pre- and post-index date (first RA claim 01JUN2009-31DEC2010) were analyzed. SIFRA was calculated for the baseline period. Healthcare costs and biologic use were examined for the follow-up period. Chi-square tests were used to find SIFRA score and outcome association. Generalized linear models were used to determine costs, and multivariate logistic regression were used to determine SIFRA effect. Results: 1, 920 RA patients were identified. Mean SIFRA score was 14.21, and 7.05 (49.57%) included clinical and functional status variables, medications: 6.32 (44.47%); radiology and laboratory results: 0.48 (3.40%), and extra-articular manifestation: 0.32 (2.25%). Controlling for age, gender, region, and comorbidity index, high SIFRA tercile patients were 5.16 times more likely to be prescribed biologics (p<0.001, CI: 3.46-7.69), and incurred higher costs €2, 091 (p<0.001, CI: €1, 557-€2, 625) than those in the low SIFRA tercile. Image/graph: Conclusions: RA severity varies in Turkey, and is a determinant of healthcare costs and biologic therapy use. Biologic use positively correlated with severity score. Future comparative effectiveness studies in RA treatment should include severity scores. Disclosure of Interest: None Declared